2013
DOI: 10.3109/01612840.2012.753558
|View full text |Cite
|
Sign up to set email alerts
|

The Experience of Seclusion and Restraint in Psychiatric Settings: Perspectives of Patients

Abstract: Many studies report that the use of seclusion and restraint (SR) is experienced negatively by patients who experience feelings of shame, helplessness, and humiliation, and may relive previous trauma events. Since 2000, in Québec, exceptional measures like SR have been framed by a protocol. This protocol provides health care teams with guidelines for relieving, containing, and reducing the suffering caused by SR. We have no knowledge, however, about the views of patients regarding application of the protocol. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
59
0
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 68 publications
(64 citation statements)
references
References 17 publications
3
59
0
2
Order By: Relevance
“…This theme connects to the theme “protest behaviour,” as patients reported that professionals reacted unnecessarily aggressively, using coercion, when patients’ “protest behaviour” escalated (Knowles et al., ; Ling, Cleverley, & Perivolaris, ; Rose, Evans, Laker, & Wykes, ). Also, patients requested the opportunity to try out other treatments, therapy, strategies or coping skills before coercive measures were initiated (Meehan et al., ; Katsakou et al., ; Kontio et al., ; Faschingbauer et al., ; Larue et al., ; Knowles et al., ).…”
Section: Results Of Literature Search and Selection Processmentioning
confidence: 99%
See 2 more Smart Citations
“…This theme connects to the theme “protest behaviour,” as patients reported that professionals reacted unnecessarily aggressively, using coercion, when patients’ “protest behaviour” escalated (Knowles et al., ; Ling, Cleverley, & Perivolaris, ; Rose, Evans, Laker, & Wykes, ). Also, patients requested the opportunity to try out other treatments, therapy, strategies or coping skills before coercive measures were initiated (Meehan et al., ; Katsakou et al., ; Kontio et al., ; Faschingbauer et al., ; Larue et al., ; Knowles et al., ).…”
Section: Results Of Literature Search and Selection Processmentioning
confidence: 99%
“…“Being subjected to professionals’ control” was characterized by patients’ reported perceptions of being physically and mentally abused (Wynn, ; Haw et al., ; Sibitz et al., ; Knowles et al., ), punished and treated like criminals by the professionals while being coerced (Meehan et al., ; Haglund et al., ; Wynn, ; Chien et al., ; Mayers et al., ; Kontio et al., ; Faschingbauer et al., ; Ling et al., ). Patients felt that their autonomy and rights had been violated (Haglund et al., ; Hoekstra, Lendemeijer, & Jansen, ; Wynn, ; Larue et al., ; Ezeobele et al., ; Larsen & Terkelsen, ; Riley et al., ), and strong feelings of humiliation were reported (Holmes et al., ; Wynn, ; Mayers et al., ; Haw et al., ; Faschingbauer et al., ; Larue et al., ; Van Wijk et al., ; Ling et al., ; Nyttingnes, Ruud, & Rugkasa, ). These experiences were exacerbated by the position of power held by professionals (Meehan et al., ; Haglund et al., ; Hoekstra et al., ; Katsakou et al., ; Kontio et al., ; Faschingbauer et al., ; Ezeobele et al., ; Knowles et al., ).…”
Section: Results Of Literature Search and Selection Processmentioning
confidence: 99%
See 1 more Smart Citation
“…losing credibility, deviating from unit or organisational regulations; Curran 2007). It is concerning that some teams underuse alternatives and relational interventions once SR protocols have been initiated (Larue et al 2009(Larue et al , 2013. Larue et al (2013), furthermore, found that the underlying causes of patient behaviour warranting an SR incident were often unexplored or attributed to a single cause.…”
Section: Staff-related Factorsmentioning
confidence: 99%
“…It is concerning that some teams underuse alternatives and relational interventions once SR protocols have been initiated (Larue et al 2009(Larue et al , 2013. Larue et al (2013), furthermore, found that the underlying causes of patient behaviour warranting an SR incident were often unexplored or attributed to a single cause. One American study by Klinge (1994) investigated differences in staff attitudes towards SR use (N ¼ 109); she found that gender and education were important factors in deciding to use SR with acutely psychotic forensic patients.…”
Section: Staff-related Factorsmentioning
confidence: 99%